2019
DOI: 10.4049/jimmunol.1801273
|View full text |Cite
|
Sign up to set email alerts
|

STAT3 Inhibition Partly Abolishes IL-33–Induced Bone Marrow–Derived Monocyte Phenotypic Transition into Fibroblast Precursor and Alleviates Experimental Renal Interstitial Fibrosis

Abstract: Previous studies of Jak–STAT inhibitors have shown promise in treating kidney diseases. The activation of Jak–STAT components is important in cell fate determination in many cell types, including bone marrow–derived cells, which are important contributors in renal interstitial fibrosis. In this study, we tested the effect of a new STAT3 inhibitor, BP-1-102, on monocyte-to-fibrocyte transition and the progression of renal interstitial fibrosis. We tested the effect of BP-1-102 in a mouse model of unilateral ure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…Previous study showed that STAT3 inhibitor, S3I-301, reduced renal fibrosis in a mouse unilateral ureteral obstruction model 35 . Furthermore, the novel STAT3 inhibitor BP-1-102 has been reported to alleviate renal interstitial fibrosis through the inhibition of bone marrow-derived monocyte transition into fibroblast precursors 24 . In cardiovascular diseases, specific STAT3 inhibition has been shown to not only downregulate IL-6induced collagen synthesis significantly but also effectively regresses the pressure overload-induced cardiac hypertrophy through reducing the fibrosis process 36 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous study showed that STAT3 inhibitor, S3I-301, reduced renal fibrosis in a mouse unilateral ureteral obstruction model 35 . Furthermore, the novel STAT3 inhibitor BP-1-102 has been reported to alleviate renal interstitial fibrosis through the inhibition of bone marrow-derived monocyte transition into fibroblast precursors 24 . In cardiovascular diseases, specific STAT3 inhibition has been shown to not only downregulate IL-6induced collagen synthesis significantly but also effectively regresses the pressure overload-induced cardiac hypertrophy through reducing the fibrosis process 36 .…”
Section: Discussionmentioning
confidence: 99%
“…It is proved that BP-1-102 not only blocks the pathways of JAK2/STAT3 and NF-κB, but also targets Bcl-xL (an important protein involved in the cross talk of apoptosis and autophagy) 23 . Furthermore, BP-1-102 has been shown to have significant effects in several disease models [22][23][24] . However, the effect of BP-1-102 on vascular inflammation and AAA progression has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that IL-33 recruits bone marrow-derived fibroblasts and inflammatory cells into the kidney, thereby producing proinflammatory factors and profibrotic molecules (Liang et al, 2017). Similarly, Zhu et al found that IL-33 induced the phenotypic transformation of bone marrow-derived monocytes into fibroblasts in a dosedependent manner, thereby leading to a marked increase in the expression of α-SMA and fibronectin (Zhu et al, 2019).…”
Section: Mechanisms Of Il33/st2 Involvement In Renal Fibrosismentioning
confidence: 98%
“…This is supported by other reports showing that epithelial STAT3 promotes type 2 inflammation in the lungs in response to HDM in mice 26 , and that pharmacological blockade of STAT3 inhibits both IL-13 and IL-17A responses to HDM 27 . As STAT3 has been reported to act as a transcriptional repressor [40][41][42] , in addition to several reports demonstrating that IL-33 activates STAT3 29,30,43 , we postulated a role for an IL-33-STAT3 axis in inhibiting dectin-1 expression in epithelial cells. Our data shows that impairing STAT3 function enhances dectin-1 gene expression, and thus establishes STAT3 as repressor of dectin-1.…”
Section: Discussionmentioning
confidence: 59%